Modern views on the problem of sepsis - V.S. Kopcha (Civic Union "Communicable Diseases Intensive Care Association", 2020)
BACKGROUND. By defining the cornerstone of sepsis as the "systemic" of the inflammatory response in the form of cytokine violations, the authors of the corresponding concept are forced to recognize the etiological factors almost all pathogens of infectious diseases, which naturally go with the increased activity of cytokines in serum. Without diminishing the importance of these components of inflammation, one should pay attention to the postulate that not only viruses and protozoa never cause sepsis, but also all non-bacterial pathogens are not etiological factors of this disease, although they lead to severe systemic reactions accompanied by an increase in the level of proinflammatory cytokines. OBJECTIVE. The purpose of the work is to draw the attention of physicians to the discrepancy between the new notions about sepsis imposed on the medical community and accepted not only by anesthetists, resuscitative surgeons and surgeons, but also by many infectionists. MATERIALS AND METHODS. A detailed analysis of the clinical case of sepsis in a young woman is presented, which, due to adequate surgical and long-term conservative therapy, has safely recovered. CONCLUSIONS. Sepsis is a generalized acyclic infectious disease of the bacterial and/or fungal etiology that develops in an immunodeficient organism with characteristic pathomorphological and pathologist changes in organs and tissues.